Carbon, weight and volume of wood necromass in a forest management plan area - Coimbra Limeira, Mathaus Messias (2020)
The necromass found in ecosystems maintains the carbon content. Following this guideline, quantification becomes a valuable attribute for efficient forest management. The study aimed to quantify a fallen and standing woody necromass in the soil, weight and carbon stock in the area of the native management plan as a subsidy to it. The sampling adopted uses the fixed area method and was carried out with the installation of a circular plot with a radius of 10 meters (314 m²). Twenty-seven plots were systematically distributed, resulting in the measurement of 806 individuals, whose inclusion criteria were diameter ≥ 5 cm and tactile-visual format the degree of deterioration of dead wood. The average volume of necromass in the region was 14.70 m³ ha-¹ with 5.37 mg ha-¹ of necromass. This value has a carbon stock of approximately 2.6 mg ha-¹. This research showed that necromass distribution in the area occurs regularly and unevenly distributed throughout the study area. The material presented has 78% of individuals with less than twenty centimeters in diameter and, for the standing material, 96.15% of individuals with less than forty centimeters. Necromass contributes to reduce CO2 concentration in the atmosphere and decrease the greenhouse effect. Contributing to the maintenance of organic matter and organic carbon helps in the recovery and cycling of nutrients and highlights the importance of carbon fixation.